Endometriosis and dyspareunia: Solving the enigma - Jose Carlos Vilches Jimenez; Lucas Lozano Romero; Ignacio Brunel Garcia; Manuel Lozano Sanchez; Rodrigo Orozco Fernandez (Elsevier, 2023)
Introduction: Endometriosis is a chronic oestrogen-dependent disease that affects 1 in 10 women of childbearing age. Half of these women have deep dyspareunia. The presence of this symptom has been shown to negatively affect your quality of life. There are few studies in the literature that address this issue and its pathophysiology remains poorly understood. Materials and methods: A case-control study has been carried out in order to assess the multi-causality of dyspareunia in patients with endometriosis. All the patients were assessed in a unit specialising in endometriosis and pelvic pain and their disease was staged using high-resolution ultrasound following the criteria of the IDEA group. The patients were divided into two groups, patients with dyspareunia n = 45 (cases) and those without it n = 55 (controls). Results: The only element that was statistically significant in explaining the dyspareunia was the presence of nodules in the retrocervical region with p = 0.000. The odds ratio of dyspareunia in the cases group was 5.3 (95 % CI 2.2-12.5). Conclusions: Dyspareunia in patients with endometriosis is strongly dependent on the presence of nodules in the retrocervical region, although there are other factors involved that remain unknown, so more studies are still needed to understand and optimally address this symptom.